Body Composition and Spasticity in Children with Unilateral Cerebral Palsy-A Case-Control Study - Lawia Szkoda; Andrzej Szopa; Andrzej Siwiec; Ilona Kwiecień-Czerwieniec; Małgorzata Domagalska-Szopa (MDPI AG, 2022)
The aim of this study was to identify the correlations between segmental body composition and the spasticity level of the affected lower limb in children with unilateral cerebral palsy (spastic hemiplegia). Additionally, an attempt was made to identify the differences in composition between the affected and unaffected lower limbs using segmental body composition analysis. This case-control study included 31 children with spastic hemiplegia aged 8 to 16 years with differing severities of spasticity in the lower limbs. The reference group consisted of a control group which included 31 peers with corresponding age and sex to the tested group. Negative correlations obtained in the statistical analysis showed that higher spasticity level in the iliopsoas muscle is associated with lower limb fat-free mass and lower limb muscle mass. Our results showed that children with spastic hemiplegia have worse parameters of body composition in the affected limb than in the unaffected one. To confirm the importance of these results, further studies are needed in a larger population which includes non-ambulatory children.